IMPLIKASI BEHAVIORAL FINANCE PADA PROSES PENGAMBILAN KEPUTUSAN INVESTASI DI MASA PENSIUN - Kannya Purnamahatty Prawirasasra (Universitas Islam Bandung, 2016)
The increasing of life expectancy and longevity, retirement is becoming an element that is important to people’s lives. Individuals will have to work longer and save more to retire in dignity. The purpose of this research is to find out the implication of the behavioral finance in the process of investment decision making in retirement. The method used is literature review. The result of this study indicate that the psychological side of investing, namely the size of the pattern of consumption, the stage of career development, self-confidence and the development environment itself are elements that can determine the investment in retirement an investor (individual).